2006
DOI: 10.4262/denkiseiko.77.285
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Particle Size, Crystal Grain Size and Core Loss of Fe-Si Compressed Cores

Abstract: Synopsis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It has been reported that the intraparticle eddy current loss in a dust core with 10 µm diameter particles is less than 1000 kW/m 3 . 17,18 Therefore, the eddy current loss in the FNAs is sufficiently small, and the experimental result is reasonable. Because no significant eddy current loss was generated for both FNAs, there is a significant difference in the hysteresis loss between these FNAs.…”
Section: -5mentioning
confidence: 79%
“…It has been reported that the intraparticle eddy current loss in a dust core with 10 µm diameter particles is less than 1000 kW/m 3 . 17,18 Therefore, the eddy current loss in the FNAs is sufficiently small, and the experimental result is reasonable. Because no significant eddy current loss was generated for both FNAs, there is a significant difference in the hysteresis loss between these FNAs.…”
Section: -5mentioning
confidence: 79%